Food security, climate change and agriculture—Gerald Nelson, IFPRI - Nelson, Gerald C. (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2011)
Gerald Nelson from IFPRI discusses the relationship between food security, climate change and agriculture.